Invasive Plants Are a Valuable Alternate Protein Source and Can Contribute to Meeting Climate Change Targets - Iyer, Ajay; Bestwick, Charles S.; Duncan, Sylvia H.; Russell, Wendy R. (Frontiers in Sustainable Food Systems, 2021)
Agriculture has come under pressure to meet global food demands, whilst having to meet economic and ecological targets. This has opened newer avenues for investigation in unconventional protein sources. Current agricultural practices manage marginal lands mostly through animal husbandry, which; although effective in land utilisation for food production, largely contributes to global green-house gas (GHG) emissions. Assessing the revalorisation potential of invasive plant species growing on these lands may help encourage their utilisation as an alternate protein source and partially shift the burden from livestock production; the current dominant source of dietary protein, and offer alternate means of income from such lands. Six globally recognised invasive plant species found extensively on marginal lands; Gorse (Ulex europeans), Vetch (Vicia sativa), Broom (Cytisus scoparius), Fireweed (Chamaenerion angustifolium), Bracken (Pteridium aquilinum) and Buddleia (Buddleja davidii) were collected and characterised to assess their potential as alternate protein sources. Amino acid profiling revealed appreciable levels of essential amino acids (19.0±1.20, 38.83±0.82, 14.71±0.34, 10.33±1.01, 22.74±0.50 and 26.38± 1.11 % protein) for Gorse, Vetch, Broom Fireweed, Bracken and Buddleia, respectively. The availability of essential amino acids was limited by protein solubility, and Gorse was found to have the highest soluble protein content. It was also high in bioactive phenolic compounds including cinnamic- phenyl-, pyruvic- and benzoic acid derivatives. Databases generated using satellite imagery were used to locate the spread of invasive plants. Total biomass was estimated to be roughly 52 Tg with a protein content of 5.2 Tg with a total essential amino acid content of 1.25 Tg ( 24%). Globally, Fabaceae were the second most abundant invasive plant family, with much of the spread in marginal lands and shrublands. Analysis of intrinsic agricultural factors revealed economic status as the emergent factor, driven predominantly by land use allocation, with shrublands playing a pivotal role in model. Diverting resources from invasive plant removal through herbicide use and/or incineration to leaf protein extraction could contribute towards delivering sustainable protein, achieving emission targets and effective land use, while simultaneously maintaining conservation of native plant species.